THE LINK BETWEEN CIRCADIAN CLOCK AND TUMORIGENESIS - Arianna DANERI; ADRIAN LUPUȘOR; Ion MOLDOVANU; Victor VOVC (Academy of Sciences of Moldova, 2021)
The circadian clock is fundamental for allowing the human body to work properly. Studies demonstrated that circadian disruption is a risk factor for a lot of pathological states and in this Review, the idea is to focus on tumorigenesis. Cancer is a social plague and it is interesting to note how the human lifestyle can be one of the most important reasons to explain the enormous spread of tumours. The crucial point described is the connection between light, melatonin and cancer genes; this triad has an important role in tumorigenesis. After that, there is a focus on breast cancer that is the most frequent in the world, and it is also demonstrated how social level and education can influence the possibility to develop cancer during life. In the end, there is a description of one of the possible new frontiers in the treatment of cancer: chronotherapy.